Establishing “Challenging Conversations” in the Exercise of Pedagogical Leadership - Loyola-Bustos, Christian (Revista Saberes Educativos, 2019)
A little over a decade ago, a series of legal modifications, programs and various lines of action have been created in order to strengthen the role of management teams, which has become a central issue within the educational policies of today. The main objective of this article is to make known the importance of teaching support through the development of “challenging conversations”, within the framework of pedagogical leadership. In addition, guidelines are outlined for the planning and analysis of a “challenging conversation”, through professional techniques and accompaniments associated with mentoring and coaching.